Esquema de escalonamento cross-layer baseado no DQCA, com reserva peri?dica de time-slots para tr?fego de voz - Guimar?es, Josias Teixeira (2011)
The DQCA (Distributed Queuing Collision Avoidance) is a high-performance and stable medium access protocol, which maintains a high throughput with any traffic load. However, it can allow very high variations in delay, especially when large messages occupy the channel for long periods and this is an undesirable behavior for traffic with constant bit rate, such as voice, which have strict requirements on Quality of service (QoS) related to delay and jitter. In this work we propose a cross-layer scheme based on DQCA protocol, which mainly aims to reduce the average delay and jitter of voice packets. This scheme, called RP-DQCA (DQCA with periodic reservation), aims to maintain the high throughput achievable with the DQCA, while improving the QoS of voice services through periodic reservation of time slots for packets of this type, according to the generation rate of the same.